Climate Change Adaptation Strategies in Community Forest User Groups of Dang District, Nepal - Acharya, Ganesh Raj; Tiwari, Krishna Raj; Acharya, Sanjaya (Banko Janakari, 2025)
This study on Climate Change Adaptation (CCA) strategies in Community Forest User Groups (CFUGs) was conducted at two levels: household and user group. The study was conducted in seven Community Forests (CFs) of Dang district, Nepal, using household questionnaires administered to 570 Households (HHs) and Focus Group Discussion (FGD) checklists. Primary data on climate change adaptation strategies were collected from both the household and group levels. This study explores the understanding of CCA strategies and climate change adaptation knowledge at the local level. The understanding of climate change is primarily shaped by its adverse effects. We identified nine different adaptation strategies at the household level, while seven different strategies were observed at the user group level. Individual preferences for adaptation practices are often those that provide immediate benefits. Similarly, at the user group level, the construction of recharge ponds and ecological restoration activities were among the most widely adopted CCA strategies with strategic importance. An Eta correlation was used to assess the relationship between household income and climate change adaptation strategies, yielding a coefficient of 0.383, indicating a relationship exists. The study concludes that CFUGs have emphasized CCA strategies as an inseparable part of their community practices, as evidenced by their choices at both the household and user group levels.